The Role of Digital Media in Transforming Communication: A Historical Perspective on Nigeria's Socio-Political Landscape - Agbaka, Joyce (Universitas Medan Area, 2025)
This study explored the impact of digital media in transforming communication within Nigeria's socio-political context. By examining the historical progression of communication technologies, it emphasizes how digital media has redefined the way information is shared and received, closed geographical gaps, and empowered marginalized communities. Using a historical research approach, this study examines archival records, government policies, and academic literature to analyze the adoption and integration of digital technologies in Nigeria's media environment. Placing Nigeria's experience within a wider historical and global framework, the study highlights the pivotal role of digital media in advancing democratic processes and redefining the country's socio-political narrative. Nonetheless, challenges such as misinformation, digital illiteracy, and inadequate infrastructure persist. The study concluded that digital media has transformed Nigeria's communication landscape, offering both opportunities for development and areas of concern. The study recommended among others that the government should establish and enforce effective policies to curb the spread of misinformation and disinformation on digital platforms while safeguarding freedom of expression. Efforts should involve partnerships with technology companies to monitor content, support fact-checking initiatives, and run public awareness campaigns to help citizens recognize and avoid false information.